A Conjugate Gradient Method with Global Convergence for Large-Scale Unconstrained Optimization Problems - Shengwei Yao; Xiwen Lu; Zengxin Wei (Journal of Applied Mathematics)
The conjugate gradient (CG) method has played a special role in solving large-scale nonlinear optimization problems due to the simplicity of their very low memory requirements. This paper proposes a conjugate gradient method which is similar to Dai-Liao conjugate gradient method (Dai and Liao, 2001) but has stronger convergence properties. The given method possesses the sufficient descent condition, and is globally convergent under strong Wolfe-Powell (SWP) line search for general function. Our numerical results show that the proposed method is very efficient for the test problems.